Joaquin de Helguero and bourbon economic thought in Piura during the early 19th century - Espinoza Claudio, César (2018)
In this paper we make a global reading of a manuscript about Piura’s 1802 economy, elaborated by Joaquin de Helguero. We present and examine the response to a «Questionnaire» submitted by the Consulate in Lima. The recorded information shows existence of a plan that reflects a methodical and rigorous approach to the functioning of an economic space, social and labor life of people who cohabit in a golden landscape of a coastal desert and mountain ranges crossing the northern territory of the Viceroyalty of Peru. In this text, we qualitatively show the heterogeneity of people and polidiversity of their productive practices, as well as dispersion and fragmentary character of indigenous economies, diversity and limits to which a type of economy had arrived that sought to transform the Political reforms of the Bourbons since mid-eighteenth century.